Internalisasi Nilai Akhlak Anak Menurut Surat Al-Luqman - Muhammad Nasir (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Understanding the concept of islamic education to children is very important thing, boys and girls are the next generation of nation that must have the value and character as expected by nation, state and religion, because the use of islamic values as the provision of life in facing the growth of individuals who called us Insal kamil. Education which inculcates the values of faith and the good deeds is a process of internalization of divine valeus which must understood by every kids who will grow and develop as the successor of the nation in the future. Looking at some important aspects of the quranic teaching are faith, worship and morals. Especially the moral education that must be applied by both parents to their children from early childhood until the age of adolescent, because many cases that occur among children of early childhood to adolescent that reflects the bad attitude and behavior, for examples kicking his friends, speak harsly and snapped at both parents. The purpose of this study is to know the method or the way of applying moral education based on sural Al-Luqman. Based on the purpose stated above, this study will use a form of inductive and deductive descriptive study based on quran surah luqman verses 12-19. The result of the study found that the story of luqman al- Hakim containing his advice to his kids about moral education and the advice should be applied by parents to their children in their family